2019
DOI: 10.1097/iae.0000000000002173
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity in Pseudoxanthoma Elasticum

Abstract: Visual impairment and blindness are frequent in PXE, particularly in patients older than 50 years. Although choroidal neovascularization is associated with the majority of vision loss, macular atrophy is also common. The proportion of visual impairment in PXE is comparable with late age-related macular degeneration but manifests earlier in life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Auto-antibodies have been described in patients with retinal degeneration, and other authors have suggested that they may form as a consequence of exposure of the immune system to retinal breakdown products. 5,6 It is unclear why this acute PXE-associated syndrome has not been described before, to my knowledge. The authors note there was a rare incidence (5%) of this acute retinopathy among their larger cohort of patients with PXE.…”
mentioning
confidence: 96%
“…Auto-antibodies have been described in patients with retinal degeneration, and other authors have suggested that they may form as a consequence of exposure of the immune system to retinal breakdown products. 5,6 It is unclear why this acute PXE-associated syndrome has not been described before, to my knowledge. The authors note there was a rare incidence (5%) of this acute retinopathy among their larger cohort of patients with PXE.…”
mentioning
confidence: 96%
“…Change in the intra-or subretinal fluid, which we defined to be signs of CNV activity, was graded as 'better', 'equal' or 'worse', based on an overall conclusion of all 25 B-scans as compared with the previous OCT-scan (as illustrated in Fig 1) In case of discrepancy, the major vote of the three graders was taken for both CNV activity and the change in CNV activity. Furthermore, the macular phenotype was assessed according to previously reported criteria and the eyes were categorized in four groups: atrophic, CNV lesions, mixed or no CNV or atrophy [5] .…”
Section: Assessment Of Outcomementioning
confidence: 99%
“…The latter results in BM breaks, socalled angioid streaks, which allow CNV to arise [2]. These cause visual impairment at a relatively young age [5] . Up to now, no causal treatment for PXE exists.…”
Section: Introductionmentioning
confidence: 99%
“…Ocular manifestations of PXE present most frequently with angioid streaks, that lead to choroidal neovascularization (CNV) which may associate with oedema, bleeding, chorioretinal atrophy and scars, and consequently loss of central vision [12,13]. The fragmentation of the elastic fibers and the calcification of the lamina elastica of the medium-sized arteries are behind the cardiovascular manifestations of PXE.…”
Section: Introductionmentioning
confidence: 99%